The segmental pattern of otx, gbx, and Hox genes in the annelid Platynereis dumerilii - Steinmetz, Patrick R. H.; Fischer, Antje; Arendt, Detlev (Evolution & development, 2011)
SUMMARY Annelids and arthropods, despite their distinct classification as Lophotrochozoa and Ecdysozoa, present a morphologically similar, segmented body plan. To elucidate the evolution of segmentation and, ultimately, to align segments across remote phyla, we undertook a refined expression analysis to precisely register the expression of conserved regionalization genes with morphological boundaries and segmental units in the marine annelid Platynereis dumerilii. We find that Pdu-otx defines a brain region anterior to the first discernable segmental entity that is delineated by a stripe of engrailed-expressing cells. The first segment is a “cryptic” segment that lacks chaetae and parapodia. This and the subsequent three chaetigerous larval segments harbor the anterior expression boundary of gbx, hox1, hox4, and lox5 genes, respectively. This molecular segmental topography matches the segmental pattern of otx, gbx, and Hox gene expression in arthropods. Our data thus support the view that an ancestral ground pattern of segmental identities existed in the trunk of the last common protostome ancestor that was lost or modified in protostomes lacking overt segmentation.